Investment Avenues Available for Teaching Professionals – An Empirical Study - Udhayasankar, R.; SELLAN, M.; B.Charumathi, Dr.; M.Sellan, M. (International Journal of Engineering and Technology, 2018)
Competitive pressures have triggered massive shifts in the style and speed of business across the globe. In this situation, financial sector has offered various avenues for investments. Investment avenues are widening in the world to create a positive sources of income. Under these circumstances, investors have their own time and choice to invest their hard-earned savings in available avenues like bank deposits schemes, postal savings scheme, provident fund (PF), share market both primary and secondary, life insurance policies (like LIC), government security or bonds (like NSC), mutual funds, real estate, gold, company deposits and other avenues for investment. Teaching professionals earn handsomely (especially after the implementation of sixth pay commission), but they seldom find time to get information about the various investment avenues. Thus, lack of financial education sets aside their disposable income in low safety, profitability and marketability of investments. As investors, teaching professional do have right to expect a good rate of return from their investment. For all these, they need adequate flow of information. Wealth creation is not an art. It is an attribute of one’s attitude towards money. How does one know whether investors have the right kind of attitude towards money? To answer this question, the present study entitled “INVESTMENT AVENUES AVAILABLE FOR TEACHING PROFESSIONALS – AN EMPIRICAL STUDY” has been taken up to understand their a) awareness level; b) investment objectives; c) preference over investment avenues, duration, financial institutions and sources of information; and d) problems in current investment decisions.